2019
DOI: 10.1002/cnma.201800578
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Oleate‐Stabilized Gd2O2S Nanoplates in Inert and Oxidizing Atmospheres

Abstract: Capping ligands play an important role in the chemistry of nanoparticles synthesized with organic surfactants. This is relevant to a number of device applications where heating may cause major modifications of crystalline nanoparticles including amorphization, surface rearrangements or sintering. Ultrathin monodisperse Ln 2 O 2 S x oxysulfide nanoparticles (Ln = lanthanide) obtained in a mixture of oleylamine, oleic acid and 1-octadecene show promising luminescence and light absorption properties. In view of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…The reaction yields were all calculated assuming that the Ln 2 O 2 S phase is formed and that 30 % of the final powder is composed of oleates, as suggested by a previous thermogravimetric analysis combined with mass spectrometry. 7 For the reactions with Gd(acac) 3 and Er(acac) 3 , both Li and Na complexes yielded a significant amount of powder (η ≈ 55 % for Er and η = 60 -90 % for Gd). Interestingly, in the case of Er, a first difference was noticed in the color of the final reaction medium, which usually is orange for Gd with Na(oleate) and pinkish with Li(acac).…”
Section: Influence Of the Nature Of Alkali Ionmentioning
confidence: 99%
“…The reaction yields were all calculated assuming that the Ln 2 O 2 S phase is formed and that 30 % of the final powder is composed of oleates, as suggested by a previous thermogravimetric analysis combined with mass spectrometry. 7 For the reactions with Gd(acac) 3 and Er(acac) 3 , both Li and Na complexes yielded a significant amount of powder (η ≈ 55 % for Er and η = 60 -90 % for Gd). Interestingly, in the case of Er, a first difference was noticed in the color of the final reaction medium, which usually is orange for Gd with Na(oleate) and pinkish with Li(acac).…”
Section: Influence Of the Nature Of Alkali Ionmentioning
confidence: 99%
“…19 We also showed that the ligands around Gd 2 O 2 S nanoparticles are oleates in bridging and chelating coordination modes. 21 Here, cerium loading is defined as y = n Ce / (n Ce + n Gd ) where n refers to the initial metallic precursor quantity in mol. The Gd/Ce ratios of the precursors introduced at the beginning of the reaction and measured by energy dispersive X-ray spectroscopy (EDX) on the isolated product were consistent (Table S1 and Figure S0), meaning that the ratio in the final powder is similar to the introduced one.…”
Section: Absorption Of Gd 2(1-y) Ce 2y O 2 S Nanoparticlesmentioning
confidence: 99%
“…However, it is also important to note that some of these methods produce compounds with low crystallinity and generate organic by-products that are difficult to remove. Eventually, these undesired products affect the particles' biological interaction and optical properties, limiting their application [123,124].…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 99%